Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus - Kottelat, Maurice (Zootaxa, 2004)
Botia kubotai, new species, is distinguished from all other species of the genus by its unique body colour pattern. In juveniles, three black stripes and five black bars leave four pairs of elongate yellow blotches; with increasing age, the bars and stripes widen, the yellow blotches become more slender and rows of small yellow spots are added in the stripes and in the bars. The nomenclature of Botiinae and the systematics of the South and Southeast Asian taxa are discussed. A new genus is named: Chromobotia (type species: Cobitis macracanthus). Hymenphysa is a synonym of Botia and species usually placed in Hymenphysa should be called Syncrossus.